Awareness and Predominance of Blue Light Related Visual Problems Among Undergraduate Medical Students: Blue Light Related Visual Problems - Prabal Bhargava; Theingi Maung Maung; Chong Phei Shan; Christina Chong Kai Thing; Diong Jing Loo; Gloria Philip; Kee Chin Hui; Christina Gellknight (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2022)
Background:As students spend more time for online class sessions by using computer, they get more prone toblue light exposure.Visual problems among the university students can have an adverse impact on their educational and employment opportunities.The aim of this study is to investigate the blue light exposure and visual problems among the undergraduate university students. Methods:A cross-sectional study was carried out in a private medical school in the Kedah state, Malaysia. Total of 200 students from pre-clinical years were taken as sample by convenient sampling method.A self-administered structured questionnaire was used, and the data were computerized and analysed by using IBM SPSS Statistics Version 22. Results: The prevalence of refractive error was 66.6% and the highest problem was short sightedness with astigmatism. Sufficient awareness towards eye problems was noticed among the respondents. More than 90% of the students showed satisfactory knowledge related to the harmful effects of blue light.Dry eyes and recent headache were associated to fluorescent light. Recent visual complaints were depending on computer exposure whilerecent headache was related to mobile use. Worsening of eye problems and computer or projector exposure were found to be associated. Conclusion: Our study highlights the constrained awareness among novice medical students regarding ocular health. We carefully discerned the pattern of blue light exposure and the prevalence of ocular symptoms and refractive errors in the studied population. Recommendations for further research that can help improve eye health were suggested.